Settling the boom : the sites and subjects of Bakken oil - Thomas, Mary E. (Mary Elizabeth), 1970-; Braun, Bruce, 1964- (University of Minnesota Press, 2023)
"Settling the Boom studies how the disruptive forces of an oil boom in the northern Great Plains are contained through the extension of settler temporalities, reassertions of heteropatriarchy, and the tethering of life to the volatility of oil and its cruel optimisms. The collection reveals the results of sustained research in Williston, North Dakota, the epicenter of the "Bakken Boom.""--